THE INFLUENCE OF MICRO AND SMALL INDUSTRIES ON ECONOMIC GROWTH WEST SUMATRA PROVINCE - Imelfina Musthafa; Hefrizal Handra; Efa Yonnedi (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
This research aims to determine the influence of the number of Micro and Small Industries (MSI), the number of MSI workers, and MSI income on the Regional Gross Domestic Product (RGDP) of West Sumatra Province. The analytical method used in this research is descriptive and quantitative analysis method. The sample for this research is the number of MSIs, number of MSI workers, MSI income and MSI RGDP from 2018 to 2020 which comes from the West Sumatra Province Central Statistics Agency consisting of 19 cities/regencies. The results of this research found that simultaneously there was a positive and significant influence of the number of MSIs, the number of MSI workers, and MSI income on the RGDP of West Sumatra Province. Government policy really needs to be implemented to create regulations that make it easier for MSI to grow and develop so that MSI has a large contribution to the RGDP of West Sumatra Province.